Impact of fruit reserve conditions from harvest to processing on the chemical composition and quality of coffee - Osorio, V.; Pabón, J.; Medina, R. (Frontiers in Sustainable Food Systems, 2024)
Changes in the different stages of fruit processing are becoming a differentiating factor in coffee quality. Currently, generating delays in the processing of the fruit, that is, reserve, is a practice that can modify the sensory profile of the beverage. In this study, the fruit was reserved in three stages of maturity, two temperatures (15° and 20°C) and at two timepoints (24 and 48 h), establishing its chemical composition and sensory characteristics using analytical techniques such as liquid and gas chromatography. The state of maturity 1 showed an effect on malic and quinic acids due to the interaction of temperature and reserve time, while stage of maturity 3 showed an effect on glucose and fructose. The state of maturity 2 showed an effect of the reserve time on the same compounds of states 1 and 3, in addition to the content of defective beans and sucrose. The sensory quality expressed as the total SCA (Specialty Coffee Association) score and the attributes did not show treatments effect, the reserve of the fruit under the evaluated conditions presents an effect on the descriptors of the flavor. Extending the fruit reserve time from 24 to 48 h showed an increase in the groups of flavor descriptors associated with fruit and red fruits from 33.33 to 66.66% and from 34.04 to 65.95%. This implies that the constituent parts of the fruit such as the exocarp and mesocarp interact with the bean, leading to changes in the chemical composition and the improvement of the qualitative complexity of the sensory quality. This is a consequence of the increase in the frequency of the flavor descriptors of the fruit and red fruit category.